Contextual Architectural Design for Horticultural Research Facility in Trenggalek - Achmad Wildan Hafidz; Farida Murti; Andarita Rolalisasi (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to formulate a design concept for a horticultural research facility in Trenggalek Regency using a contextual architectural approach. The method used is descriptive qualitative through literature study, analysis of regional planning documents, and precedent studies of similar buildings. The results show that a horticultural research facility requires the integration of research, production, and educational functions within a unified spatial system. In addition, zoning arrangements, controlled circulation, and environmental systems that support research activities are necessary. The “Bhumi Loka” concept is formulated as the design foundation, emphasizing the relationship between land as the primary medium of horticulture and space as a container for human activities. This concept produces a contextual, sustainable design approach that aligns with the agricultural characteristics of Trenggalek.